ARTERIAL HYPERTENSION (HT) IS ONE OF THE MOST PREDICTIVE RISK FACTORS FOR TYPE 2 DIABETES (DM2). THE FINDRISC IS VALIDATED FOR THE EARLY DETECTION OF SUFFERING FROM DM2. (June 2022) - Mirada, Micaela; Pessana, Franco; Acuña, Maria Isabel Rodriguez; Ramirez, Agustin; Sanchez, Ramiro
Abstract : Objective: To investigate in patients with hypertension the risk of DM 2 according to the criteria of the FINDRISC score Design and method: Cross-sectional epidemiological study. 659 subjects between 18–65 years of age, 210 (32%) female and 449 (68%) males were selected. The parametric variables under the studio were: Age, Weight, Height, Central Abdominal Perimeter, Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), HDL, LDL, Total cholesterol, triglycerides, Basal blood glucose and the dichotomous variables: Sex, Diet, Exercise, antihypertensive drugs, historical hyperglycemia, family history of DM to evaluate the FINDRISC score. Two multivariate analysis model was used: linear and potential regression, together with logical tests. Excel and JMP were used for the statistical analysis. Results: From the group studied, 71% of them were at risk of developing type 2 diabetes mellitus. Among them, 16.2% (107 subjects) presented high and very high FINDRISC score values (15–20 and greater than 20). 25.8% were hypertensives (131 patients), and 36% of them present a high and very high risk FINDRISC score value, compared with only 11% of the normotensive group. When analyzing the population of hypertensive subjects and high risk for diabetes, no differences were observed between male and female (37% male men and 33% female. Conclusions: With FINDRISK score, Hypertension is one of the most relevant risk factors to develop diabetes in our population. This makes it possible to plan individual actions in order to achieve a reduction in cardiovascular complications.